Islamic Ecotheology and Contemporary Environmental Activism: A Living Qur'an Analysis of the Pandawara Group - Khanif, Arkan; Heriyanto, H; Nurdin, Yanyan (Universitas Muhammadiyah Surakarta, 2026)
Existing studies on environmental activism and Green Islam in Indonesia largely focus on normative theology, institutional religious responses, or policy frameworks, while neglecting how Qur'anic ecological values are performatively embodied within youth-led digital movements. Moreover, scholarship on the Living Qur'an and Islamic ecotheology has insufficiently examined how theological legitimacy is constructed through digital virality and netizen participation, leaving a gap in understanding the transformation of ecological piety in the digital age. This article presents an in depth analysis of the Pandawara Group, a youth-led environmental movement, through the lenses of the Living Qur'an and Islamic Ecotheology. Employing a qualitative method with a netnographic design, this study analyzes viral content and netizen interactions to explore how theological values such as khalifah (vicegerency), amanah (trust), and the prohibition of fasad (corruption) are performatively expressed. The findings indicate that Pandawara practices what this study terms